2013
DOI: 10.1007/s11999-012-2749-x
|View full text |Cite
|
Sign up to set email alerts
|

Orthopaedic Surgeons’ Knowledge and Misconceptions in the Identification of Intimate Partner Violence Against Women

Abstract: Background Intimate partner violence (IPV)-physical, sexual, psychologic, or financial abuse between intimate partners-is the most common cause of nonfatal injury to women in North America. As many IPV-related injuries are musculoskeletal, orthopaedic surgeons are well positioned to identify and assist these patients. However, data are lacking regarding surgeons' knowledge of the prevalence of IPV in orthopaedic practices, surgeons' screening and management methods, and surgeons' perceptions about IPV. Questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…These perceptions correspond fairly well with national and international reports of IPV incidence rates (see e.g., Black et al ., ; Nybergh et al ., ). Compared with previous findings, where the general public overestimated (see e.g., Beeble et al ., ) and healthcare providers underestimated (see e.g., Della Rocca et al ., ) IPV prevalence, the estimates in the present sample were more in line with recent prevalence statistics. It is possible that public awareness and education campaigns in recent years have made the Swedish population relatively knowledgeable about IPV prevalence.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These perceptions correspond fairly well with national and international reports of IPV incidence rates (see e.g., Black et al ., ; Nybergh et al ., ). Compared with previous findings, where the general public overestimated (see e.g., Beeble et al ., ) and healthcare providers underestimated (see e.g., Della Rocca et al ., ) IPV prevalence, the estimates in the present sample were more in line with recent prevalence statistics. It is possible that public awareness and education campaigns in recent years have made the Swedish population relatively knowledgeable about IPV prevalence.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings on respondents’ victim‐blaming attitudes suggest that people tend to overlook the complexity that victims face when weighting the pros and cons of staying in an abusive relationship, consistent with previous reports in the literature (Anderson & Saunders, ; Baly, ; Gracia, ; Meyer, ; Waltermaurer, ; Yoshihama, ). In line with victim blame research (see e.g., Bhandari et al ., ; Della Rocca et al ., ; Sprague et al ., ; West & Wandrei, ; Worden & Carlson, ), our respondents believed that IPV victims are to some degree responsible for the violence and able to put an end to the abuse. Such blameful responses, when expressed to victims, can increase victims’ self‐blame and negatively affect the likelihood of them acting proactively against the abuse (Flood & Pease, ).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…These findings were supported by a similar evaluation of US surgeon members of the Orthopaedic Trauma Association which found that among 153 surgeon members of the Orthopaedic Trauma Association, several misconceptions were evident: 1) victims must be getting something out of the abusive relationships (16%); 2) some women have personalities that cause the abuse (20%); and 3) the battering would stop if the batterer quit abusing alcohol (40%). In the past year, only 4% of respondents currently screened for IPV among female patients with injuries [9]. …”
Section: Reviewmentioning
confidence: 99%